Analysis of Warm Water Compresses as An Intervention of Gout Arthritis with Acute Pain Problems in Elderly Families - Arita Murwani; Nuryati Nuryati; Anna Nur Hikmawati; RR Viantika Kusumasari; Riza Yulina Amri (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Gout arthritis is a metabolic bone disorder caused by the abnormal metabolism of purines characterized by increased levels of uric acid in the blood, causing pain in the local supply. One of the therapies that can be used to reduce the scale of pain in Gout arthritis patients is warm water compresses. Objective: Analyze the effect of warm water compresses on the pain scale in Gout arthritis patients—Method: Descriptive design with a case study approach. Results showed a difference in the pain scale before and after warm water administration compresses in Gout arthritis patients. Conclusion: Warm water compresses are effective for lowering the scale of pain in patients with Gout arthritis because they can reduce muscle spasms, stimulate pain, cause vasodilation and increase blood flow. Blood vessels will dilate, which improves blood circulation in these tissues